Efficiency improvement of three phase squirrel cage induction motor by controlling the applied voltage to the stator using SIMULINK models - Altaira, Murad, author; Collins, George J., advisor; Suryanarayanan, Siddharth, committee member; Ackerson, Christopher, committee member (Colorado State University. Libraries, 2018)
Optimizing the efficiency of three phase squirrel cage induction motors (SCIMs) plays a big role in saving electric energy consumption. The purpose of this thesis is to maximize the efficiency of three phase (SCIM) when it runs at speeds greater than the speed at which the efficiency is maximum during normal operation, i.e., rated voltage by decreasing the applied voltage to the stator using MATLAB/SIMULINK. Equivalent circuit and parameter identification of three phase (SCIM) are explained. MATLAB/SIMULINK is employed to identify the motor parameters and to simulate a three phase (SCIM) under different loads. The effect of reducing the voltage on motor characteristics such as the produced torque by the motor, power factor, reactive power, apparent power, output power, rotor speed and magnetizing current is explained.